Six, Seven or Eight Coordinate FeII, CoII or NiII Complexes of Amide‐Appended Tetraazamacrocycles for ParaCEST Thermometry. Issue 50 (23rd October 2015) - Olatunde, Abiola O.; Bond, Christopher J.; Dorazio, Sarina J.; Cox, Jordan M.; Benedict, Jason B.; Daddario, Michael D.; Spernyak, Joseph A.; Morrow, Janet R.
Abstract: Fe II, Co II and Ni II complexes of two tetraazamacrocycles (1, 4, 8, 11‐tetrakis(carbamoylmethyl)‐1, 4, 8, 11‐tetraazacyclotetradecane (L1 ) and 1, 4, 7, 10‐tetrakis(carbamoylmethyl)‐1, 4, 7, 10‐tetraazacyclododecane (L2 ) show promise as paraCEST agents for registration of temperature (paraCEST=paramagnetic chemical exchange saturation transfer). The Fe II, Co II and Ni II complexes ofL1 show up to four CEST peaks shifted ≤112 ppm, whereas analogous complexes ofL2 show only a single CEST peak at ≤69 ppm. Comparison of the temperature coefficients ( C T ) of the CEST peaks of [Co(L2 )] 2+, [Fe(L2 )] 2+, [Ni(L1 )] 2+ and [Co(L1 )] 2+ showed that a CEST peak of [Co(L1 )] 2+ gave the largest C T (−0.66 ppm  o C −1 at 4.7 T). NMR spectral and CEST properties of these complexes correspond to coordination complex symmetry as shown by structural data. The [Ni(L1 )] 2+ and [Co(L1 )] 2+ complexes have a six‐coordinate metal ion bound to the 1‐, 4‐amide oxygen atoms and four nitrogen atoms of the tetraazamacrocycle. The [Fe(L2 )] 2+ complex has an unusual eight‐coordinate Fe II bound to four amide oxygen atoms and four macrocyclic nitrogen atoms. For [Co(L2 )] 2+, one structure has seven‐coordinate Co II with three bound amide pendents and a second structure has a six‐coordinate Co II with two bound amide pendents. Abstract : Changes in coordination affect MRI contrast : The remarkably different chemical exchange saturation transfer (CEST) spectra of Co II, Fe II or Ni II complexes of amide‐appended macrocycles is based on the different coordination geometries for complexes of the two ligands. The complexes with the most highly shifted CEST peaks show promise for the development as magnetic resonance imaging (MRI) temperature probes for thermometry.